Optimalisasi Protokol Kesehatan Melalui Edukasi Yang Berkelanjutan Di Era New Normal : Optimalisasi Protokol Kesehatan Melalui Edukasi Yang Berkelanjutan Di Era New Normal - Setyorini, Andri; Hartiningsih, Sri Nur; Musdalifah, Musdalifah; Asty Salsabilah, Alifiah (Jurnal Pengabdian Masyarakat Kesehatan Terkini, 2023)
Background: The Covid-19 pandemic has been going on since the end of 2019 and has made people have to fight hard to maintain their survival. Compliance with the behavior of maintaining the 5 M health protocol in this new adaptation period needs to be seriously encouraged by the community, so that transmission can be prevented and minimize the incidence of contracting the virus. Activities: This service activity is Education and Counseling about Optimizing the Application of Health Protocols through Continuous Education in the New Normal Era which is given to PKK mothers in Trimurti Village Rt 08 Kapanewon Srandakan Bantul. Purpose: to increase public knowledge and compliance in optimizing the implementation of health protocols in the new normal era. Implementation Method: The implementation of this community service is carried out offline using 3 sessions, namely: Session 1: Education on Optimizing Health Protocols Through Continuous Education in the New Normal Era; Session 2: Counseling and Sharing involving the community; Session 3: Evaluation. Conclusion: the level of knowledge after being given health education increases to 100%. Then in terms of adherence to health protocols after being given health education as much as 85% were in the compliant category. Suggestion: It is better for the public to maintain health protocols and regularly participate in health education activities related to Covid-19 as a form of updating the latest information to prevent transmission of Covid-19 in the new normal era.